In vitro antifungal activity of extracts and alkaloid compounds from Piper arboreum against dermatophytes - Fabiana Brusco Lorenzetti; Carla Maria Mariano Fernandez; Eliana Harue Endo; Regina Yasuko Makimori; Mariza Barion Romagnolo; César Armando Contreras Lancheros; Marcia Regina Pereira Cabral; Maria Helena Sarragiotto; Celso Vataru Nakamura; Tânia Ueda Nakamura; Ludmila Pini Simões; Benedito Prado Dias Filho (International Journal of Plant Based Pharmaceuticals)
Piper is widely distributed in subtropical regions and species of this genus are known for their potent pharmacological activities. Piper arboreum Aubl. is a traditional medicinal plant popularly known as "pau-de-angola", "jaborandi", and chili pepper, demonstrating antifungal, trypanocidal, antibacterial, and antioxidant activities. The leaves of P. arboreum were extracted using Soxhlet and dichloromethane to obtain the extract, which was then fractionated using solvents of different polarities. Samples were analyzed using ultra-high-performance liquid chromatography coupled with mass spectrometry equipped with an electrospray ionization source. Antifungal microdilution assays were performed, and scanning and transmission electron microscopy were used to assess the invasion of the pretreated nail. The minimum inhibitory concentration (MIC) values of the extract and a dichloromethane fraction were, respectively, 62.5 μg/ml and 16.0 μg/ml against Trichophyton rubrum, and 125 μg/ml and 62.5 μg/ml, and 500 μg/ml and 500 μg/ml against T. mentagrophytes, and Microsporum gypseum, respectively. No growth was observed on nail fragments exposed to the extract (at concentrations > 64 µg/ml and then inoculated with spore suspension. Transmission electron microscopy revealed strong inhibition of hyphal growth and an irregular growth pattern following treatment with the extract and the dichloromethane fraction. Results demonstrated the antifungal properties of the P. arboreum extract and its dichloromethane fraction against dermatophytes, with the identification of three different alkaloid compounds. The cytotoxicity was specific towards the fungal cells, and morphological and ultrastructural analyses indicated damage to the cell wall and cytoplasmic membrane as the potential mechanism of action. The leaf material used to generate the extract can be taken from the plant without any detrimental effect thus enabling strategies to be implemented for the exploitation of this species.